Non-Destructive Testing and Kinematic Limit Analysis Applied to a Historic Masonry Church Early Intervened with Rc Elements - Barrientos-Monsalve, M (Elsevier Ltd, 2025)
This article assesses the structural condition of a historic unreinforced masonry (URM) church whose original earthquake-resistant system was strengthened with reinforced concrete (RC) elements after the 1927 Mendoza earthquake. This early intervention, which took place between 1927 and 1930, consisted of RC frames formed by beams and columns embedded in the existing masonry. Since then, the church s seismic performance has been satisfactory, presenting minor damage after significant earthquakes. Despite its successful seismic performance, this church −and its strengthening strategy- has not been studied in depth. Due to the limited structural information available, a multidisciplinary study involving several non-destructive tests (NDT) in the church was conducted to understand its current structural state and reduce information gaps derived from historical sources and visual on-site inspection surveys. NDTs included the use of Terrestrial Laser Scanner (TLS), Unmanned Aerial Vehicle (UAV) photogrammetry, and Ground Penetrating Radar (GPR), among others. To assess the effectiveness of RC interventions, seismic behavior before and after the different retrofitting interventions was compared through linear kinematic analyses of the main failure mechanisms observed. The research results show that RC interventions increased the spectral accelerations required to activate overturning mechanisms in the macro-elements identified in the church, with safety indexes exceeding 1.0 for most RC-intervened macro-elements. The latter indicates that these elements are safe under the seismic loads specified by the Chilean code for heritage structures. © 2024 Elsevier Ltd
Keywords: Historic church; Strengthening intervention; Kinematic analysis; NDT